Sir Robert Sibbald’s ’Directions for his honoured friend Mr Llwyd how to Trace and Remarke the Vestiges of the Roman Wall betwixt Forth and Clyde.’ - Haverfield, F J; MacDonald, George (Proceedings of the Society of Antiquaries of Scotland, 1910)